2021
DOI: 10.7554/elife.66768
|View full text |Cite
|
Sign up to set email alerts
|

miR-1 coordinately regulates lysosomal v-ATPase and biogenesis to impact proteotoxicity and muscle function during aging

Abstract: Muscle function relies on the precise architecture of dynamic contractile elements, which must be fine-tuned to maintain motility throughout life. Muscle is also plastic, and remodeled in response to stress, growth, neural and metabolic inputs. The conserved muscle-enriched microRNA, miR-1, regulates distinct aspects of muscle development, but whether it plays a role during aging is unknown. Here we investigated Caenorhabditis elegans miR-1 in muscle function in response to proteostatic stress. mir-1 deletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 62 publications
0
22
1
Order By: Relevance
“…The member of the microphthalmia family of basic helix-loop -helix-leucine-zipper (bHLH-Zip) including transcription factor EB (TFEB), transcription factor E3(TFE3) as well as a microphthalmia-associated transcription factor (MITF) participate in the mitochondrial dynamics in the kinase PINK1 and ubiquitin ligase Parkin -dependent manner [ 105 ]. Furthermore, TFEB also controls lysosome biogenesis and coordinating the lysosomal functions [ 106 ]. For instance, ATPase pumps (ATP6V1H, Na+/K- ATPase) and lysosomal membrane proteins (LAMP1 and LAMP2) and lysosomal proteases (cathepsin D, cathepsin B).…”
Section: Discussionmentioning
confidence: 99%
“…The member of the microphthalmia family of basic helix-loop -helix-leucine-zipper (bHLH-Zip) including transcription factor EB (TFEB), transcription factor E3(TFE3) as well as a microphthalmia-associated transcription factor (MITF) participate in the mitochondrial dynamics in the kinase PINK1 and ubiquitin ligase Parkin -dependent manner [ 105 ]. Furthermore, TFEB also controls lysosome biogenesis and coordinating the lysosomal functions [ 106 ]. For instance, ATPase pumps (ATP6V1H, Na+/K- ATPase) and lysosomal membrane proteins (LAMP1 and LAMP2) and lysosomal proteases (cathepsin D, cathepsin B).…”
Section: Discussionmentioning
confidence: 99%
“…Our results do not exclude the existence of a secondary signal from muscle to neurons that could improve motility. Indeed, previous work has identified the miRNA mir-1 , as a regulator of a retrograde signal from muscle to neurons that modulates neuronal activity (Simon et al 2008) and mir-1 inactivation improves worm motility under pathological conditions (Schiffer et al 2021). Interestingly, mammalian SRF has been shown to negatively regulate mir-1 expression (Zhang et al 2011; Tritsch et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of age-related protein aggregation, miR-1 was shown to regulate muscle function and improve pharyngeal pumping in response to proteotoxic stress over time, while also suppressing polyglutamine 35 (polyQ35) protein aggregation in C. elegans [ 30 ]. A v-ATPase subunit, vha-13 was identified as a direct target of miR-1, which regulates lysosomal biogenesis and function [ 30 ]. Thus, miR-1 should be studied as a putative therapeutic strategy for combating muscle-specific protein aggregation and improving muscle motility across the lifespan.…”
Section: The Role Of Mirna Regulation In Age-related Autophagic Decli...mentioning
confidence: 99%
“…Notably, studies in centenarians have provided more knowledge about how dynamic human miRNA profiles are throughout aging [ 27 , 28 ] For instance, increased biogenesis of miRNAs is observed in centenarians compared with octogenarians [ 29 ]. More recent studies showed that miRNAs regulate age-associated processes, and some evidence links miRNAs to protein aggregation in mammalian tissues, namely in the brain and skeletal muscle [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%